2020
DOI: 10.1155/2020/6120580
|View full text |Cite
|
Sign up to set email alerts
|

Adult Spinal Deformities: Can Patient-Specific Rods Change the Preoperative Planning into Clinical Reality? Feasibility Study and Preliminary Results about 77 Cases

Abstract: Surgical management of adult spinal deformities remains challenging, and one of the major goals is to restore sagittal alignment. Spinal rods used for posterior fixation are usually delivered straight and bended manually during surgery. This manual bending can be responsible for undercorrection of the deformity. In the last years, prebended patient-specific rods have been developed and might be a valuable tool in order to optimize surgical results. The objective is therefore to use the time between sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“… 6 In a separate 3 month post-operative evaluation of outcomes of 77 patients, the authors found the planning and use of the rods provided significant improvement in SVA and PI-LL. 7 They again noted, as have previous studies, that PT was improved, but less predictable. They also reported on 86 patients with at least 1 year follow-up.…”
Section: Resultssupporting
confidence: 68%
“… 6 In a separate 3 month post-operative evaluation of outcomes of 77 patients, the authors found the planning and use of the rods provided significant improvement in SVA and PI-LL. 7 They again noted, as have previous studies, that PT was improved, but less predictable. They also reported on 86 patients with at least 1 year follow-up.…”
Section: Resultssupporting
confidence: 68%
“…Prost and Pesenti later evaluated 77 patients at 3 months following ASD correction surgery involving PSRs, finding a similar improvement in SVA (mean 27.1 ± 8.6 mm, p < 0.0001), interestingly greater in patients with Parkinson’s disease (MD 53 mm, p < 0.005) [ 12 ]. Farah et al also presented data on 12 patients with Parkinson’s disease, reporting improvement at 1 year follow-up (MD 76.1 mm, P = 0.013) [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…74 A study examining 43 ASD cases using PSRs with no intraoperative adjustments to the prebent rods found improvements in SVA and PI-LL, confirming the clinical feasibility of their use. 14 Other studies have demonstrated strong and stable treatment effects at a 2-year follow-up in patients treated with PSRs, with particular improvements noted in SVA and PI-LL. 75 Two armed studies comparing PSRs to the current standard of care are lacking.…”
Section: How Do Psrs Compare To Traditional Rods?mentioning
confidence: 93%
“…71,80 Lastly, exact knowledge of rod curvature preoperatively will allow further postoperative analysis and improved surgical planning research. 14,67…”
Section: How Do Psrs Compare To Traditional Rods?mentioning
confidence: 99%
See 1 more Smart Citation